Merry-or-Worry, Illusion. (April 2022) - Bachmann, Talis
Ambiguous figures (aka bistable, multistable, or reversible images) have fascinated scientists as well as laypersons for centuries. It may be surprising indeed how one and the same physical depiction can be experienced in perceptual awareness in cardinally different ways. In the most well-known examples of such illusions of multistability, the phenomenal change relates just to visual organization. Much less common are perceptions of alternating emotional content in the ambiguous visual image. Here, I introduce one such example.